Extensive submandibular desmoid fibromatosis in a pediatric patient: A therapeutic challenge - Sabah Abdulaziz Issa; Hussein Ali Abdulnabi (Elsevier, 2020)
Desmoid fibromatosis is a progressive benign connective tissue tumor, with a high tendency toward local invasiveness and recurrence. The tumor occurs mostly during childhood, involving the head and neck in 11-15% of the cases. Complete surgical excision with a safe margin is the standard treatment. While adjuvant non-surgical therapy is often considered for incomplete excision or recurrences. A 6-year-old female patient came with a rapidly growing non-painful mass of 6 months duration, involving lower jaw region on the left side. Examination revealed a significantly large and firm non-mobile mass involving the left mandibular and submandibular region, with limited mouth opening. The lesion appeared on imaging as an expansile heterogeneous mass, with evidence of destructive bony changes involving the mandible. Incisional biopsy initially performed followed by surgical excision with segmental resection of the mandible. Without adjuvant therapy, no recurrence observed during >2 years follow up period, and bone grafting subsequently performed. Head and neck pediatric fibromatosis is a rare and aggressive tumor, and its management often constitutes a major challenge to the clinicians. Surgical excision with preservation of cosmetic and functional demands and long-term follow up often result in good outcomes, and adjuvant therapy usually reserved for recurrence or gross residual lesions.